Period1 gates the circadian modulation of memory‐relevant signaling in mouse hippocampus by regulating the nuclear shuttling of the CREB kinase pP90RSK. Issue 5 (September 2016) - Rawashdeh, Oliver; Jilg, Antje; Maronde, Erik; Fahrenkrug, Jan; Stehle, Jörg H.
Abstract: Memory performance varies over a 24‐h day/night cycle. While the detailed underlying mechanisms are yet unknown, recent evidence suggests that in the mouse hippocampus, rhythmic phosphorylation of mitogen‐activated protein kinase (MAPK) and cyclic adenosine monophosphate response element‐binding protein (CREB) are central to the circadian ( 24 h) regulation of learning and memory. We recently identified the clock protein PERIOD1 (PER1) as a vehicle that translates information encoding time of day to hippocampal plasticity. We here elaborate how PER1 may gate the sensitivity of memory‐relevant hippocampal signaling pathways. We found that in wild‐type mice (WT), spatial learning triggers CREB phosphorylation only during the daytime, and that this effect depends on the presence of PER1. The time‐of‐day‐dependent induction of CREB phosphorylation can be reproduced pharmacologically in acute hippocampal slices prepared from WT mice, but is absent in preparations made from Per1‐knockout (Per1 −/− ) mice. We showed that the PER1‐dependent CREB phosphorylation is regulated downstream of MAPK. Stimulation of WT hippocampal neurons triggered the co‐translocation of PER1 and the CREB kinase pP90RSK (pMAPK‐activated ribosomal S6 kinase) into the nucleus. In hippocampal neurons from Per1 −/− mice, however, pP90RSK remained perinuclear. A co‐immunoprecipitation assay confirmed a high‐affinity interaction between PER1 and pP90RSK. Knocking down endogenous PER1 in hippocampal cells inhibited adenylyl cyclase‐dependent CREB activation. Taken together, the PER1‐dependent modulation of cytoplasmic‐to‐nuclear signaling in the murine hippocampus provides a molecular explanation for how the circadian system potentially shapes a temporal framework for daytime‐dependent memory performance, and adds a novel facet to the versatility of the clock gene protein PER1. We provide evidence that the circadian clock gene Period1 (Per1) regulates CREB phosphorylation in the mouse hippocampus, sculpturing time‐of‐day‐dependent memory formation. This molecular mechanism constitutes the functional link between circadian rhythms and learning efficiency. In hippocampal neurons of wild‐type mice, pP90RSK translocates into the nucleus upon stimulation with forskolin (left), whereas in Period 1‐knockout ( Per 1 −/− ) mice (right) the kinase is trapped at the nuclear periphery, unable to efficiently phosphorylate nuclear CREB. Consequently, the presence of PER1 in hippocampal neurons is a prerequisite for the time‐of‐day‐dependent phosphorylation of CREB, as it regulates the shuttling of pP90RSK into the nucleus. Representative immunofluorescence images show a temporal difference in phosphorylated cAMP response element‐binding protein (pCREB; green color) levels in all regions of the dorsal hippocampus between a wild‐type C3H mouse (WT; left) and a Period1‐knockout ( Per 1 −/− ; right) mouse. Images were taken 2 h after lights on, thus, when fluctuating levels of pCREB peak in WT mouse hippocampus. Insets show a representative hippocampal neuron, in response to activating cAMP signaling, stained for the neuronal marker NeuN (red), the nuclear marker DAPI (blue) and the activated CREB kinase pP90RSK (green). The image was taken 2 h after light onset (at the peak of the endogenous CREB phosphorylation that fluctuates with time of day). Magnification: 100X, inset 400X. Read the Editorial Highlight for this article on page650 . Cover image for this issue: doi:10.1111/jnc.13332 . Abstract : We provide evidence that the circadian clock gene Period1 (Per1) regulates CREB phosphorylation in the mouse hippocampus, sculpturing time‐of‐day‐dependent memory formation. This molecular mechanism constitutes the functional link between circadian rhythms and learning efficiency. In hippocampal neurons of wild‐type mice, pP90RSK translocates into the nucleus upon stimulation with forskolin (left), whereas in Period 1‐knockout ( Per 1 −/− ) mice (right) the kinase is trapped at the nuclear periphery, unable to efficiently phosphorylate nuclear CREB. Consequently, the presence of PER1 in hippocampal neurons is a prerequisite for the time‐of‐day‐dependent phosphorylation of CREB, as it regulates the shuttling of pP90RSK into the nucleus. Representative immunofluorescence images show a temporal difference in phosphorylated cAMP response element‐binding protein (pCREB; green color) levels in all regions of the dorsal hippocampus between a wild‐type C3H mouse (WT; left) and a Period1‐knockout ( Per 1 −/− ; right) mouse. Images were taken 2 h after lights on, thus, when fluctuating levels of pCREB peak in WT mouse hippocampus. Insets show a representative hippocampal neuron, in response to activating cAMP signaling, stained for the neuronal marker NeuN (red), the nuclear marker DAPI (blue) and the activated CREB kinase pP90RSK (green). The image was taken 2 h after light onset (at the peak of the endogenous CREB phosphorylation that fluctuates with time of day). Magnification: 100X, inset 400X. Read the Editorial Highlight for this article on page650 . Cover image for this issue: doi:10.1111/jnc.13332 .